2018
DOI: 10.1039/c7tc04114d
|View full text |Cite
|
Sign up to set email alerts
|

Microscale electrohydrodynamic printing of conductive silver features based on in situ reactive inks

Abstract: An electrohydrodynamic printing strategy is presented to fabricate microscale flexible features with tunable conductive properties based on in situ reactive inks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…The resistance of the fabricated silver conductive line can be as low as 4 × 10 −4 Ω•m. Lei [25] developed an electrohydrodynamic (EHD) jet printing strategy based on in situ reactive inks to fabricate microscale conductive silver features. The printed features mainly contain nanoscale silver particles and exhibit an electrical conductivity of 3.3 × 10 −4 Ω•m.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of the fabricated silver conductive line can be as low as 4 × 10 −4 Ω•m. Lei [25] developed an electrohydrodynamic (EHD) jet printing strategy based on in situ reactive inks to fabricate microscale conductive silver features. The printed features mainly contain nanoscale silver particles and exhibit an electrical conductivity of 3.3 × 10 −4 Ω•m.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effects of the reactive ink concentration, printing layer number, and treatment temperature on the electrical properties and microstructures of the printed patterns were investigated systematically. Compared with the literature reports [28,30,31,32,33,34], the advantages of our work are that it does not require special experimental setups. The conductivity of the conductive pattern could be controlled easily by changing the concentrations of the reductant and the reaction ink.…”
Section: Introductionmentioning
confidence: 93%
“…To address these issues, particle-free in situ reactive inks have been recently developed, with great advantages in their simple, low-cost fabrication process and high conductivity using relatively low treatment temperature [30,31,32,33,34,35,36,37,38]. Bidoki et al reported that deposited layers of in situ reactive silver inks exhibited high electrical conductance of up to 1.89 × 10 5 S/m [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works reported the deposition of conductive silver tracks on tracing and glossy paper substrate using silver-reactive ink for the development of electronic devices. [16][17][18] As mentioned by Yang et al sulfuric paper has low permeability, low surface roughness, and good heat resistance that allows post-treatment at 200 1C, making them a good candidate for deposition of conductive silver tracks. 18 However, the low permeability of such substrate renders them unfit for the development of microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%